Market transformations as collaborative change: Institutional co‐evolution through small business entrepreneurship. (18th April 2022) - Westman, Linda; Luederitz, Christopher; Kundurpi, Aravind; Mercado, Alexander Julian; Burch, Sarah Lynn
Abstract: Entrepreneurship may be one entry point to trigger transformations toward sustainability. Yet, there is limited knowledge on the ability of small‐ and medium‐sized enterprises (SMEs) to play a role in transformation processes, beyond the initial stages of niche innovation. Building on data collected through 125 interviews in Toronto, Vancouver and London, we examine perceived contributions of SME‐led sustainable entrepreneurship to market transformations. Our data show that sustainable entrepreneurs face significant constraints in individually exercising influence over mass markets, as they encounter social forces that generate resistance to change. However, SMEs are able to act collaboratively to shape transformation processes. We propose three mechanisms of institutional co‐evolution that capture these contributions: network learning, collective norm‐construction and collaborative advocacy.